O protagonismo sertanejo e a crítica a história oficial:representações do Contestado por meio do estudo dos romances históricos Geração do Deserto (1964) e o Reino Místico dos Pinheirais (2011) - Linn, Natiely Aparecida (2024)
In this research, we intend to analyze the representations built around the Contestado War, more specifically the way in which the subjects who took part in this conflict are portrayed. To do this, we selected two sources - from different time periods - belonging to the historical novel literary genre: Geração do Deserto (1964), by Guido Wilmar Sassi; and O Reino Místico dos Pinheirais (2011), by Wilson Joel Leal Gasino. One of the aims of this work is to explore the way in which the Contestado sertanejos were characterized by the novelists over time, taking into account the historical context in which each author wrote and published their work. As for the geographical space delimited for this research, it should be said that there are no fixed borders, as it comprises contested territory, which was disputed by the states of Paraná and Santa Catarina at the beginning of the 20th century. In this sense, considering that this is a work on the history of the contested region, it is worth highlighting the importance of working on the issue of identity, since there is a predominance of an officialized view in the southern region, which has resulted in the construction of perspectives that privilege the presence and protagonism of European immigrants and end up excluding other subjects who were present in this environment, such as, for example, sertanejos, poor immigrants, indigenous people, adventurers, escaped slaves, women, among others. Thus, it is possible to state that this work also aims to contribute to the deconstruction of officialized versions of the history, showing, through the study and importance of literature as a source for History, the different possibilities of telling and analyzing the protagonism of historically marginalized subjects, who populated and populate not only the states of Paraná and Santa Catarina, but all of Brazil.